The Influence of Harvest Time and Drying Time on Total Flavonoid Contents of Psidium Guajava Folium - Rahmawati, Meilani Nur; Susilowati, Susilowati; Sesaningrum, Fany Putri Enjang (Indonesian Journal of Global Health Research, 2024)
Psidium guajava L. have been used to treat or prevent various diseases such as diarrhea, flatulence, anti-inflammatory, antioxidant, antimicrobial and anticancer. Flavonoids are biomarker compounds responsible for their activity. However, harvest and post-harvest stages of plant may change flavonoid content. The present work investigates harvest time and drying time variations of quality and total flavonoids content of Guava leaves. Method: Guava leaves was collected in the morning (9 am), evening (3 pm), and dried for 24, 36 and 48 hours. Each simplisia was tested for macroscopic and loss drying contents. Total flavonoids in each extract were determined as quercetin by UV-Visible spectrophotometry, then comparative analysis was performed with One Way Anova. Total flavonoid levels harvested in the afternoon were higher (1.0887 mgQE/g) than in the morning (0.7200 mgQE/g), while drying time for 24 hours (0.24507 mg QE/g) showed the highest flavonoid levels compared to drying for 36 hours and 48 hours significantly. This indicates that guava leaves are best harvested in the afternoon and dried for 24 hours.